Web-Based Warehouse Logistics and Inventory Management Application Using the Priority Queue Algorithm (Case Study: PT Arga Morini Indotama) - Rosalina; Statiswaty Statiswaty; Ryan Rinaldi Hadistio (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
PT Arga Morini Indotama is a nickel mining company whose warehouse logistics and inventory management activities are still handled manually, potentially causing delays in information processing, recording errors, and difficulties in monitoring stock availability. This study aims to design and develop a web-based logistics and warehouse inventory management application to improve the effectiveness of inventory management. The system was developed using the Rational Unified Process (RUP) methodology, which consists of four phases: inception, elaboration, construction, and transition. The application implements the Rank Order Centroid (ROC) method to determine the priority weights of decision criteria and the Priority Queue algorithm to prioritize goods requests based on stock criticality, departmental urgency, and frequency of use. The application was developed using PHP, the Laravel framework, and MySQL as the database management system. System testing was conducted using Black Box Testing and User Acceptance Testing (UAT) involving 12 respondents. The results indicate that the Priority Queue algorithm successfully prioritizes goods requests accurately and consistently with manual calculations. The UAT results show an average user acceptance rate of 85.84%, consisting of 85.84% for efficiency and productivity, 85.84% for functional suitability, 84.17% for performance efficiency, and 87.50% for user interface and user experience. Therefore, the developed system is considered feasible for supporting logistics and warehouse inventory operations at PT Arga Morini Indotama more effectively, efficiently, and accurately, while also supporting inventory management decision-making. The system is also expected to improve logistics service quality, accelerate the goods request process, and minimize administrative errors in warehouse inventory management.